2022
DOI: 10.3389/fnagi.2022.1060734
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS-based brain functional response to robot-assisted training for upper-limb in stroke patients with hemiplegia

Abstract: BackgroundRobot-assisted therapy (RAT) has received considerable attention in stroke motor rehabilitation. Characteristics of brain functional response associated with RAT would provide a theoretical basis for choosing the appropriate protocol for a patient. However, the cortical response induced by RAT remains to be fully elucidated due to the lack of dynamic brain functional assessment tools.ObjectiveTo guide the implementation of clinical therapy, this study focused on the brain functional responses induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Several studies have utilized fNIRS to compare cortical activity before and after upper limb training with robotic devices in patients who have experienced a stroke. [11][12][13][14][15] One study conducted robot-assisted therapy in stroke patients with hemiplegia, using fNIRS to compare cortical activity between groups with severe and moderate impairments. [13] However, to the best of our knowledge, few studies are using fNIRS to compare cortical activity after training with a robotic device and conventional device for upper limb rehabilitation in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have utilized fNIRS to compare cortical activity before and after upper limb training with robotic devices in patients who have experienced a stroke. [11][12][13][14][15] One study conducted robot-assisted therapy in stroke patients with hemiplegia, using fNIRS to compare cortical activity between groups with severe and moderate impairments. [13] However, to the best of our knowledge, few studies are using fNIRS to compare cortical activity after training with a robotic device and conventional device for upper limb rehabilitation in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Several studies have utilized fNIRS to compare cortical activity before and after upper limb training with robotic devices in patients with stroke. [11][12][13][14][15] However, there is a particular paucity of research comparing the effects of robotic versus conventional devices on cortical activity during upper limb rehabilitation in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that stroke patients exhibit right hemispheric involvement in compensation when compared to healthy individuals. A study investigating brain function in patients with different levels of motor dysfunction [ 29 ] discovered that patients with severe dysfunction displayed considerable hemispheric functional connectivity in the upper-limb motor assistance mode, bilaterally involving prefrontal, motor, and occipital areas, in contrast to patients with moderate dysfunction. Furthermore, the study revealed a significant increase in the involvement of ipsilateral assistive motor areas in the functional brain network.…”
Section: Nirs As a Monitoring Toolmentioning
confidence: 99%
“…In stroke patients, most resting-state functional connectivity studies are based on the a priori selection of seed regions [15] , which cannot provide information on the brain-wide change characteristics of FC, so there is a need for brain-wide static functional connectivity studies to investigate the underlying neurobiological mechanisms. The brain is a highly synergistic and integrated network, and continuous and uninterrupted intrinsic brain activity is an important feature of healthy brain function [16] [17] . It has been found that functional connectivity re ects neuroanatomical features that allow assessment of the intrinsic transmission of neural information within the network [18] [19] , and that resting-state brain activity spatially organises neural activity in a speci c coherent pattern.SFC, a model and data-driven algorithm based on resting-state fMRI, is characterised by the absence of hypothetical analyses of a priori knowledge, and the whole-brain-wide ROIs of Intergroup variability analysis can clarify the interaction mechanism between ROIs.…”
Section: Introductionmentioning
confidence: 99%